Comparative Analysis of Pre Roll Advertising On Youtube using AIDMA - Handayani, Trianita Adhi; Hudrasyah, Herry (Journal of Business and Management, 2015)
Abstract - Based on research conducted by Nielsen to Youtube in 2013, visitors to YouTube now reached more than 1 billion visitors per month worldwide. Youtube is now ranked as the fourth most visited site in the world in Indonesia. The high Youtube’s visitor traffic in Indonesia became a magnet for companies to advertise on the site Youtube. There’s a lot of company that invest their money to advertise their brand using Youtube as the media. The most familiar kind of advertising in Youtube is pre-roll ads which has two kinds, skippable and non skippable pre roll ads. Even though a lot of people got annoyed with this form of ads, YouTube still keep it exists. It means that, this form of advertisement still gave an impact to the brand or product. This problem will be analyzed by measuring and comparing the effectiveness between skippable and non skippable pre roll ads on Youtube using AIDMA and also by collecting behavioural substance of netizen in Bandung. Each of the phases will be measured and will be compared to find which form is more effective. Research is conducted using qualitative and quantitative research. For qualitative, researcher conduct interview to figure the substance behavior pattern of netizen in Bandung. For quantitative research, questionnaire is distributed to 200 respondents with a pre test conducted to 30 respondents. Questionnaire is distributed to netizen in Bandung who have ever access YouTube and ever found pre roll ads while accessing YouTube. There are two types of data analysis, which is descriptive and comparative analysis. All of analysis is processed using SPSS. Indicators used in the questionnaire is proven valid and reliable. Finally, the effectiveness of both pre roll ads can be analyzed by every phase of AIDMA. Over all, skippable pre roll ads is more effective than non skippable pre roll ads. One of the reason is because skippable pre roll ads involve viewers to watch the ads even though only for the first five seconds but it could make viewers easier to recognize and remember the brand that appear on pre roll ads. From the result we also know that people tend to watch the ads while waiting to skip on the skippable pre roll ads, and people tend to ignore the ads when they found non skippable pre roll ads. Keywords : Pre Roll Advertising, YouTube, online advertising, AIDMA, skippable and non skippable ads.